Decreased TLR4 expression on monocytes may cause regulatory T cells abnormality in patients with primary immune thrombocytopenia. (4th July 2017) - Hao, Yating; Li, Huiyuan; Li, Yang; Lyu, Mingen; Zhang, Donglei; Fu, Rongfeng; Guan, Yue; Wang, Shixuan; Sun, Boyang; Dou, Xueqing; Yang, Renchi
Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disease with many immune dysfunctions including T helper type 1 cell (Th1) polarization and regulatory T cells (Tregs) deficiency. This study aimed to determine the effects of TLR4 on Treg differentiation and the cytokine production of peripheral blood mononuclear cells (PBMCs) from patients with ITP. We found that expression of TLR4 on monocytes was significantly decreased in patients with active ITP than that in healthy controls and it had positive correlation with platelet count. However, there was no expression of TLR4 on CD4 + T cells. The result of further experiments in vitro showed that lipopolysaccharide (LPS) stimulation could enhance TLR4 expression on monocytes. Additionally, activation of TLR4 with LPS could promote differentiation of Treg cells and anti-TLR4 attenuated this effect. There was no significant difference about Th17 cells among three subgroups. However, the Th17/Treg cell ratio was decreased after stimulation with LPS and increased with anti-TLR4. Moreover, activation of TLR4 with LPS could significantly promote the secretion of interleukin-10 (IL-10) and transforming growth factor-β1 (TGFB1), while anti-TLR4 significantly suppressed the secretion of them. Nevertheless, the secretion of IL-17A did not reach the statistical difference among three subgroups. In summary, decreased TLR4 appears to cause Tregs abnormality in ITP by modulating Tregs differentiation and immunoregulatory cytokines.